The Body of His Glory Resurrection Imagery in Philippians 3:20–21 - Schmisek, Brian (2013)
In the entire Pauline corpus, the term “body” is used with respect to resurrection in only two verses: 1 Corinthians 15:44 and Philippians 3:20–21. In neither case does it mean resuscitated flesh. In Philippians, Paul modifies the term body by “glory,” which he uses to express the radiant presence of God, in which Christ now and ultimately in which all believers will share. This article will attempt to show that for Paul the Risen Christ's “body of glory” is a term that indicates Christ's presence with God, rather than a descriptive phrase about properties of the resurrected body. The article concludes with some modest pastoral and theological implications.
Keywords: Philippians; Phil 3:20–21; Glory; Body; body of glory; Paul; Resurrection